Performance Analysis of Turbo Codes - Sedy, Jakub; Silhavy, Pavel; Krajsa, Ondrej; Hrouza, Ondrej (Communications - Scientific Letters of the University of Zilina, 2013)
The article focuses on the performance analyses of Turbo Codes. These codes belong to the group of error correction codes. By their use, it is possible to achieve high system performance. The performance analysis is based on simulations for different code parameters that affect the code gain, bit error rate and computational complexity. Furthermore, it presents the basic structure of the encoder and decoder and the principle of encoding and decoding, which uses the Viterbi algorithm with soft input and soft output.
Keywords: turbo encoder; turbo decoder; iterative decoding; SOVA; BER